Biomechanical analysis of the stability of anterograde reamed intramedullary nails in femoral spiral fractures. (April 2020) - Herrera, A.; Rosell, J.; Ibarz, E.; Albareda, J.; Gabarre, S.; Mateo, J.; Gracia, L.
Highlights: Spiral fractures are the most complicated from a biomechanical point of view, because they present high instability. Intramedullary nailing has emerged as an alternative in the treatment of that type of fractures. A numerical study of reamed locked intramedullary nails in spiral femoral fractures along zones 2 and 4 of wiss is done. Blocked reamed nails can be considered as an appropriate surgical technique in the treatment of spiral femoral fractures. Blocked reamed nails provide sufficient stability in order to obtain an adequate fracture healing. Abstract: Femoral shaft fractures present high morbidity and important complications and consequences, being spiral fractures the most complicated from a biomechanical point of view, being unstable and without possibility of getting a good contact between nail and femoral endosteum. Femoral diaphyseal fractures are treated, usually, by means of intramedullary nailing. So, it is necessary to know the osteosynthesis stability and which locking screws combination is optimal. This work studies the use of reamed locked intramedullary nails in spiral femoral fractures located along zones 2 and 4 of wiss, depending on the spire length, corresponding to 32-A spiral type in AO/OTA classification, which represent a percentage of 23% within the total of diaphyseal fractures. A three-dimensional finite element model of the femur was developed, modeling a spiral fracture with different spiral lengths and gaps. A femoral nail was used, considering two transversal screws both at the proximal and the distal parts. The study was focused on the immediately post-operative stage, verifying the appropriate stability of the osteosynthesis. Reamed intramedullary blocked nails provide appropriate stability of femoral spiral fractures, considering global mobility of femoral head with respect to femoral condyles, relative displacements between fragments at fracture site, stresses at nail and locking screws, and stresses at cortical bone. The obtained results show that the use of blocked reamed nails in spiral femoral fractures can be considered as an appropriate surgical technique, providing sufficient stability in order to obtain an adequate fracture healing.